QUALITY OF SERVICE ANALYSIS OF WICO NETWORK GRAPARI TELKOM PURWOKERTO USING TIPHON STANDARD - Hidayat, Rizky Bagas Nur; Oktaviana, Luzi Dwi; Kuncoro, Adam Prayogo (Jurnal Teknik Informatika (Jutif), 2024)
The main problem of providing internet services for provider companies, especially WiCo GraPARI Telkom Purwokerto in responding to the needs and challenges of technological digitalization. This research aims to analyze the Quality of Service (QoS) of WiCo GraPARI Telkom Purwokerto network using TIPHON standard. The TIPHON standard is a series of standards developed by ETSI (European Telecommunications Standards Institute) in order to support the interoperability of Internet Protocol (IP) based telecommunications services. Testing of throughput, delay, packet loss, and jitter parameters was carried out using the Wireshark application. Testing quality of service parameters is done through four scenarios in quiet and crowded internet network conditions for the process of downloading and uploading videos from Google Drive. The results show that the overall network performance falls into the "Very Good" category with an index of 4 for throughput, delay, and packet loss, and the "Good" category with an index of 3 for jitter. The highest throughput was recorded at 23.687564 bps, the lowest delay was 0.386 ms, with no packet loss in all scenarios, and the lowest jitter was 0.386 ms. Thus, it can be concluded that the WiCo GraPARI Telkom Purwokerto internet network has met the expected TIPHON quality standards. Suggestions for future research to be able to include the expansion of studies in various other WiCo GraPARI locations to get a more comprehensive picture as well as the use of other testing methods and tools for more varied and in-depth results.